PERANCANGAN MESIN PENCACAH SAMPAH ORGANIK DENGAN SISTEM PENGGERAK MOTOR BENSIN - Rean Gavriel Putra Karundeng, - (2022)
Organic waste is a type of waste that ranks first in the quantity produced annually in Indonesia amounting to 60% of the total weight of 64 million tons of waste every year. The need for a useful chopping machine is needed to be able to reduce waste parts to make it easier to recycle waste. With the implementation of calculations to determine the elements of the machine and the finite element analysis method, the research the establishment of an organic waste chopping machine with a gasoline motor drive system produced a compact chopping machine frame with dimensions of 130 cm x 60 cm x 90 cm. It uses a gasoline motor with a power of 5.5 HP and a predetermined blade rotation worth 500 rpm. The maximum voltage test of the AISI 304 material for the frame got a value of 5.693x107 N/m2 and the AISI 1035 material for the blade got a value of 1.766x107 N/m2. The calculation of the capacity in chopping organic waste is 1548 kg/hour for dry stems and leaves, 144 kg/hour for thatch grass and 132 kg/hour for hay.